A New Hybrid ICI-SC Scheme for OFDM Systems - Geeta Arora, Ritu Chaudhary, (International Journal of Scientific Research and Management (IJSRM), 2015)
Orthogonal Frequency Division Multiplexing (OFDM) is an optimum technique for 4G broadband multimedia wireless systems. OFDM suffers from the effect of frequency offset caused by mobility which disturbs the orthogonality between subcarriers and results in Inter Carrier Interference (ICI). ICI leads to system performance impairments. Many ICI cancellation methods have been proposed to cancel or reduce the effect of ICI. This paper presents a new ICI Self-Cancellation scheme (Hybrid Self-Cancellation) by combining two techniques. In proposed scheme, the Real Constant Weighted Data Conversion (RCWDC) Scheme and Improved Weighted Conjugate Transformation (IWCT) Scheme are put together which will minimizes the effect of ICI on adjacent subcarriers. In terms of BER and CIR, the Hybrid scheme gives better results compared to that existing Self Cancellation scheme.